MIMO fractional order control of a water tank plant - Rojas–Moreno, Arturo (2019)
This work implements a MIMO (Multiple Input Multiple Output) FO (Fractional Order) control system for controlling the level and temperature of the water inside a tank by means of two inflow rates: cold and hot water, which are mixed to produce an outflow rate. Such a process exhibits coupling between inputs and outputs. A linear model of the plant is obtained experimentally. Such a model, the transfer matrix function of the plant, is used to design a centralized MIMO IO (Integer Order) controller that permits to achieve complete decoupling between the set points of level and temperature and the corresponding controlled outputs: level and temperature in the tank. The MIMO FO controller is obtained making fractional all de transfer functions of the MIMO IO controller. Experimental results demonstrate that the MIMO FO control system improves the control performance of the plant outputs: level and temperature of the water in the tank.